Junius Laoli TRANSFORMASI MEDIA PEMBELAJARAN PADA MATA PELAJARAN PEKERJAAN DASAR TEKNIK OTOMOTIF DI MASA PANDEMI COVID 19: Transformasi, Media, Pekerjaan Dasar Teknik Otomotif - Ahmad Suffendi; Junius Laoli (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study was to describe the transformation of learning media in automotive engineering basic work subjects during the covid 19 pandemic. This type of research was descriptive research. The collection technique used observation, interviews, and documentation. Data analysis techniques used Miles and Huberman's interactive analysis model included data collection, data reduction, data presentation, and drawing conclusions. The results showed that the transformation of learning media on basic automotive engineering subjects during the covid 19 pandemic was carried out well using What'sApp and Google classroom. The media used by the teacher were pictures, videos, softcopy and hardcopy, giving worksheets, and modules. The value that appears in students is the value of the character of reading/literacy and creative. Facilities and infrastructure were in the form of laptops, computers, smartphones, internet quotas, and wifi. The obstacles were difficulties in managing learning time and making learning more conducive, internet quotas owned by students and communication devices owned by students, and difficulties in using online media during learning. The solution in dealing with the application of learning media in basic automotive engineering work subjects during the COVID-19 pandemic was to provide guidance and direction to keep learning even though online during the pandemic. The teacher gives the material to the students in the form of a softfile with a small/light capacity. The teacher provided internet quota assistance and provides hardcopies for the students. To conclude, the transformation of learning media on basic automotive engineering subjects during the covid 19 pandemic was carried out well.